Efek Antiplasmodium Ekstrak n-Heksan Kulit Batang Mundu (Garcinia dulcis Kurz.) pada Mencit Jantan Swiss Webster yang Diinduksi Plasmodium berghei - Rosa Juwita Hesturini; Gunawan Pamudji Widodo; Mamik Ponco Rahayu (Jurnal Farmasi Indonesia, 2011)
Mundu (Garcinia dulcis Kurz.) is one of the potential with the chemical compound xanton and triterpenoid for antiplasmodial. The purpose of this study was to determine the activity of n-hexane extract of stem bark Mundu (Garcinia dulcis Kurz.) as the antiplasmodial in mice induced by Plasmodium berghei through a reduction in parasitemia and to find out the most effective doses that have antiplasmodial activities. The animal test mice before treatment with extract induced by Plasmodium berghei to the number of erythrocytic in the blood of 107 and antelmintika were given pirantel pamoat. The concentrate extract was tested in each group of animals test with a dose of 50 mg/kgBW mice, 100 mg / kgBW mice and 150 mg/kgBW mice, negative control group were given 0,5 % CMC and the positive control were given chloroquine be suspention in CMC solution. Antiplasmodial effect was observed by calculating the decrease of the amount of paracitemia. The results showed that the n-hexane extract of Mundu’s stem bark dose 50 mg / kgBW, 100 mg/kgBW and 150 mg/kgBW provide as antiplasmodial activity. Dose of 50 mg/kgBW provide antiplasmodial activity more effective.